A comparison between orthodontic model analysis using conventional methods and iModelAnalysis - Vita Previa Indirayana; Gita Gayatri; N. R. Yuliawati Zenab (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Model analysis constitutes an essential aspect of orthodontic diagnostic practice. Pavan has developed an application to simplify the mathematical calculations employed in orthodontic model analysis. Purpose: This study was conducted to obtain the differences in results and time periods of model analysis using conventional means and iModelAnalysis. Methods: The research represented a comparative analytic study. The populations comprised dental casts dating from 2014 in the Orthodontics Laboratory of Padjadjaran University. The samples comprised 31 dental casts which were subjected to a total sampling method consisting of two treatments; a conventional method calculation and one using iModelAnalysis. A normality test was conducted and processed using a paired t-test with α=0.05. Results: The means of arch length discrepancies were 1.64±2.63 mm and 1.37±3.07 mm for the conventional methods and 1.65±2.43mm and 1.42±3.04mm for iModelAnalysis. The results of a Bolton analysis for conventional methods were 78.05±2.69% and 91.93±1.29%, while those for iModelAnalysis were 77.91±2.70% and 91.96±2.13%. A Howes analysis of conventional methods produced a result of 45.56±2.83%, while for an iModelAnalysis one of 45.56±2.85%. Pont analysis for conventional methods was 39.35±0.04 mm and 49.17±2.55 mm, while for iModelAnalysis it was 39.35±0.07 mm and 49.19±2.57mm. The mean of the duration of analysis using conventional methods was 1703.81±56.46 seconds, while for iModelAnalysis it was 990.06±34.87 seconds. A normality test confirmed that the data was normally distributed (p>0.05). The results of a paired sample t-test with p>0.05 showed that there was no significant difference between the results of each analysis, while there was significant difference in the time period of analysis. Conclusion: There was no difference in the analysis results. However, there was difference in the time period of analysis between conventional methods and that of iModelAnalysis.